Experience of Daratumumab in Relapsed/Refractory Multiple Myeloma: A Multicenter Study from Turkiye - Tekinalp, Atakan; Geduk, Ayfer; Akdeniz, Aydan; Demirsoy, Esra Terzi; Gursoy, Vildan; Ak, Muzeyyen Aslaner; Ceneli, Ozcan (Galenos Publ House, 2023)
Objective: This study aimed to evaluate patients with relapsed/ refractory multiple myeloma (RRMM) who underwent daratumumab (DARA) therapy. Materials and Methods: This multicenter retrospective study included 134 patients who underwent at least two courses of DARA from February 1, 2018, to April 15, 2022. Epidemiological, disease, and treatment characteristics of patients and treatment-related side effects were evaluated. Survival analysis was performed. Results: The median age at the start of DARA was 60 (range: 35-88), with 56 patients (41.8%) being female and 48 (58.2%) being male. The median time to initiation of DARA and the median follow-up time were 41.2 (5.1223) and 5.7 (2.1-24.1) months, respectively. The overall response rate after DARA therapy was 75 (55.9%), and very good partial response or better was observed in 48 (35.8%) patients. Overall survival (OS) and progression-free survival (PFS) for all patients were 11.6 (7.8-15.5) and 8.0 (5.1-10.9) months, respectively. OS was higher for patients undergoing treatment with DARA and bortezomib-dexamethasone (DARA-Vd) compared to those undergoing treatment with DARA and lenalidomide-dexamethasone (DARA-Rd) (16.9 vs. 8.3 months; p=0.014). Among patients undergoing DARA-Rd, PFS was higher in those without extramedullary disease compared to those with extramedullary disease (not achieved vs. 3.7 months; odds ratio: 3.4; p<0.001). The median number of prior therapies was 3 (1-8). Initiation of DARA therapy in the early period provided an advantage for OS and PFS, although it was statistically insignificant. Infusion-related reactions were observed in 18 (13.4%) patients. All reactions occurred during the first infusion and most reactions were of grade 1 or 2 (94.5%). The frequency of neutropenia and thrombocytopenia was higher in the DARA-Rd group (61.9% vs. 24.7%, p<0.001 and 42.9% vs. 15.7%, p<0.001). Conclusion: Our study provides real-life data in terms of DARA therapy for patients with RRMM and supports the early initiation of DARA therapy.
Relaps/Refrakter Multipl Myelomda Daratumumab Deneyemi: Türkiye’den Çok Merkezli Bir Çalışma
Keywords: Daratumumab; Relapsed/refractory multiple myeloma; Real-world data